Analysis of the interface pressure exerted by the Chêneau brace in patients with double-curve adolescent idiopathic scoliosis - Ahmad, Asliza; Abu Osman, Noor Azuan; Mokhtar, Abdul Halim; Mehmood, Waqas; Kadri, Nahrizul Adib (SAGE Publications, 2019)
The Chêneau brace has proven its effectiveness in treating the adolescent idiopathic scoliosis patients. However, no studies reported on the analysis of interface pressure in double-curve adolescent idiopathic scoliosis patients. In this study, we evaluated the interface pressure of the Chêneau brace action in double-curve adolescent idiopathic scoliosis patient treatment. A total of 72 (60 girls and 12 boys) patients aged 10 years and above participated in the study. The F-Socket transducers (9811E) were used to evaluate the pressure on the right thoracic and left thoracolumbar curves between normal and maximum strap tension and variation in these interface pressures with other tasks. Each patient was asked to do nine different tasks corresponding to daily activities, and the interface pressures for each activity were recorded for both normal and maximum tension. The resultant mean peak pressure in double-curve adolescent idiopathic scoliosis was higher for right thoracic curves than left thoracolumbar curves in all tasks. The pressure significantly increased at the task of maximal inspiration (p < 0.0001) for both types of curves for normal and maximum tension. The degrees of correction for the thoracic and thoracolumbar curves were 23.2% and 34.5%, respectively, after 6 months of brace use (23 h per day). Hence, we could not find any substantial correlation between mean peak pressure in the standing position and degree of scoliosis correction for two curves having r = 0.158, p = 0.356 and r = –0.024, p = 0.889 values. © IMechE 2019.